Assessment of extended-spectrum β-lactamases and integrons among Enterobacteriaceae in device-associated infections: multicenter study in north of Iran. Issue 1 (December 2016) - Bagheri-Nesami, Masoumeh; Rafiei, Alireza; Eslami, Gohar; Ahangarkani, Fatemeh; Rezai, Mohammad; Nikkhah, Attieh; Hajalibeig, Azin
Abstract Background Device-associated nosocomial infections (DA-NIs), due to MDREnterobacteriaceae, are a major threat to patient safety in ICUs. We investigated on Extended-spectrum β-lactamases (ESBL) producingEnterobacteriaceae and incidence of integrons in these bacteria isolated from ventilator-associated pneumonia (VAP) and catheter-associated urinary tract infections (CAUTIs) in 18 governmental hospitals in the north of Iran. Methods In this cross-section study, the antibiotic susceptibility test was performed using the MIC method; also, phenotypically detection of ESBL-producing bacteria was carried out by the double-disk synergy (DDS) test. Presence of ESBL-related genes and integron Classes 1 and 2 was evaluated by the PCR method. Results Out of a total of 205 patients with DA-NIs, Enterobacteriaceae were responsible for (72.68%) of infections. The most common DA-NIs caused byEnterobacteriaceae were VAP (77.18%), CAUTI (19.46%), and sepsis due to VAP (3.35%). The most frequentlyEnterobacteriaceae were;Klebsiella pneumoniae 75 (24; 32% ESBL positive), E. coli 69 (6; 8.69% ESBL positive) andEnterobacter spp . 5 (5; 100% ESBL positive). Distribution of ESBL-related genes was as follows: bla-SHV (94.3%), bla-CTX (48.6%), bla-VEB (22.9%) and bla-GES (17.14%). The incidence rate of integron class 1 and class 2 was (82.92%) and (2.9%) respectively. Eight types of ESBL-producing bacteria were observed. Conclusions Due to the fact that the emergence rate of ESBLEnterobacteriaceae is increasing in DA-NIs, co-incidence of different types of ESBL genes with integrons in 75–100% of strains in our study is alarming for clinicians and healthcare safety managers. Therefore, regional and local molecular level estimations of ESBLs that are agents of DA-NIs are critical for better management of empiric therapy, especially for patients in ICUs.